Limit of consistency and agricultural importance of soils from the central Amazonian region - Corrêa, José Carlos (Pesquisa Agropecuaria Brasileira, 2014)
With the purpose of determining the upper limit of the range of water content suitable for mechanised land preparation, the consistency of a heavy textured Yellow Latosol and a medium textured Red-Yellow Podzolic soil was studied at the EMBRAPA Experiment Station located at the km 30 of the Manaus-Itacoatiara highway (State of Amazonas, Brazil). The degree of plasticity of these soils ranged from medium to high, which means that they should not be tilled when the water content is above the lower limit of plasticity. For the Yellow Latosol this limit ranged from 40% to 42% of moisture, on a plot not under agricultural use and between 42% to 43%, for a cultivated plot. For the Red-Yellow Podzolic soil the limit lies between 29% to 30%. Within each soil unit there was a trend for increasing the lower limit of plasticity with increasing organic matter.